COMPARATIVE ANALYSIS OF GROWTH PARAMETERS OF SOYBEAN AND SUNFLOWER FEED RATIONS IN BROILER PRODUCTION - Godfrey ONUWA (Stefan cel Mare University of Suceava, 2020)
The purpose of this paper is to analyze the potentials of soybean and sunflower feed rations on the growth parameters of broilers. The study was carried out at the Department of Agricultural Extension and Management, Federal College of forestry, Jos, Plateau state. One hundred (100) day old broiler chicks were purchased and divided into two (2) groups (A and B) with three (3) replicates in each group. Group A were fed with soybean feed ration, while Group B was fed with sunflower feed ration over a period of eight (8) weeks. Descriptive, proximate analysis and statistical ratios were used in analyzing data for the study. Feed A is composed of soybean meal (55%), groundnut cake (40%) and yellow maize (15%), while feed B is composed of sunflower (55%) groundnut cake (40%) and yellow maize (15%). The result of the proximate analysis indicated that each feed ingredients contained crude protein, crude fiber, ash and fat in significant quantities. The survival rate for the duration of the feeding trials for treatment B was significant at 97%. The estimate of daily weight gain was significant for treatment B from week 1 to week 4 and week 5 to week 8 with an index of 0.205 and 0.537 respectively. Also, the feed conversion ratio for treatment B was significant. While the Protein efficiency ratio was significant for treatment A. The implication of these findings suggests that sunflower was a very palatable poultry feed ration, with significant effects on the growth parameters of broilers.